2018
DOI: 10.1182/blood-2018-01-826693
|View full text |Cite
|
Sign up to set email alerts
|

Comparable outcomes of patients eligible vs ineligible for SWOG leukemia studies

Abstract: Patients may be deemed ineligible for a clinical trial for reasons that do not directly impact efficacy or safety. We identified reasons for ineligibility and compared outcomes of ineligible with eligible patients treated on Southwest Oncology Group (SWOG) Leukemia Committee protocols. Patients enrolled in SWOG phase 2, 2/3, or 3 protocols open since 2005 were analyzed for eligibility status, reasons for ineligibility, baseline characteristics, Eastern Cooperative Oncology Group (ECOG) performance status (PS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…72 One ongoing multinational trial of an HMA combination for patients who previously had failed treatment with an HMA requires patients to have been administered the HMA for higher risk disease and excludes patients who initially were treated with an HMA at a time when they had lower risk disease, even if they have higher risk features at the time of proposed clinical trial enrollment. Approximately 10% of enrolled patients later were found to have been ineligible due to minor laboratory abnormalities or assessments out of the treatment window, but only after they had been treated similarly to eligible patients.…”
Section: Narrow Enrollment Criteria and Sponsors With Limited Experiementioning
confidence: 99%
See 1 more Smart Citation
“…72 One ongoing multinational trial of an HMA combination for patients who previously had failed treatment with an HMA requires patients to have been administered the HMA for higher risk disease and excludes patients who initially were treated with an HMA at a time when they had lower risk disease, even if they have higher risk features at the time of proposed clinical trial enrollment. Approximately 10% of enrolled patients later were found to have been ineligible due to minor laboratory abnormalities or assessments out of the treatment window, but only after they had been treated similarly to eligible patients.…”
Section: Narrow Enrollment Criteria and Sponsors With Limited Experiementioning
confidence: 99%
“…The ineligible patients had rates of grade 3 to 5 adverse events, response rates, and overall survival similar to those of eligible patients. 72 One ongoing multinational trial of an HMA combination for patients who previously had failed treatment with an HMA requires patients to have been administered the HMA for higher risk disease and excludes patients who initially were treated with an HMA at a time when they had lower risk disease, even if they have higher risk features at the time of proposed clinical trial enrollment. Although this exclusion reflects the HMA label in some countries, which is restricted to higher risk disease, the eligibility criteria apply to all centers, even in locations in which HMAs commonly are used for patients with lower risk disease.…”
Section: Narrow Enrollment Criteria and Sponsors With Limited Experiementioning
confidence: 99%
“…Toxicity was also felt to be equivalent with no difference in grade 5 (fatal) adverse events between cohorts. 1 This study highlights the administrative and organizational barriers to trial enrollment, as ineligibility in most cases was attributable to administrative burdens of documentation or out-of-window laboratory or pathology data. Ineligible patients did not exhibit different survival than eligible patients, which suggests that restrictive criteria, particularly with regard to short study windows, may not affect clinical outcomes.…”
mentioning
confidence: 91%
“…Baseline disease and patient characteristics among eligible and ineligible patients, including Eastern Cooperative Oncology Group performance status, were similar. 1 The authors assessed outcomes among eligible and ineligible patients. In 6/8 of evaluable trials, there was no difference in complete remission (CR) rates between eligible and ineligible patients.…”
mentioning
confidence: 99%
“…They also noted no association between organ function eligibility criteria and subsequent organ toxicity. Analyses of 13 Southwest Oncology Group (SWOG) leukemia studies reported that 10% of almost 2500 subjects enrolled and treated in these studies were found retrospectively to be ineligible [18]. However, eligible and excluded subjects had similar frequencies of adverse events, remission rates, and survival.…”
mentioning
confidence: 99%